Multiplexed Elimination of Wild-Type DNA and High-Resolution Melting Prior to Targeted Resequencing of Liquid Biopsies. (1st October 2017) - Ladas, Ioannis; Fitarelli-Kiehl, Mariana; Song, Chen; Adalsteinsson, Viktor A; Parsons, Heather A; Lin, Nancy U; Wagle, Nikhil; Makrigiorgos, G Mike
Abstract: BACKGROUND: The use of clinical samples and circulating cell-free DNA (cfDNA) collected from liquid biopsies for diagnostic and prognostic applications in cancer is burgeoning, and improved methods that reduce the influence of excess wild-type (WT) portion of the sample are desirable. Here we present enrichment of mutation-containing sequences using enzymatic degradation of WT DNA. Mutation enrichment is combined with high-resolution melting (HRM) performed in multiplexed closed-tube reactions as a rapid, cost-effective screening tool before targeted resequencing. METHODS: We developed a homogeneous, closed-tube approach to use a double-stranded DNA-specific nuclease for degradation of WT DNA at multiple targets simultaneously. The No Denaturation Nuclease-assisted Minor Allele Enrichment with Probe Overlap (ND-NaME-PrO) uses WT oligonucleotides overlapping both strands on putative DNA targets. Under conditions of partial denaturation (DNA breathing), the oligonucleotide probes enhance double-stranded DNA-specific nuclease digestion at the selected targets, with high preference toward WT over mutant DNA. To validate ND-NaME-PrO, we used multiplexed HRM, digital PCR, and MiSeq targeted resequencing of mutated genomic DNA and cfDNA. RESULTS: Serial dilution of KRAS mutation-containing DNA shows mutation enrichment by 10- to 120-fold and detection of allelic fractions down to 0.01%. Multiplexed ND-NaME-PrO combined with multiplexed PCR-HRM showed mutation scanning of 10–20 DNA amplicons simultaneously. ND-NaME-PrO applied on cfDNA from clinical samples enables mutation enrichment and HRM scanning over 10 DNA targets. cfDNA mutations were enriched up to approximately 100-fold (average approximately 25-fold) and identified via targeted resequencing. CONCLUSIONS: Closed-tube homogeneous ND-NaME-PrO combined with multiplexed HRM is a convenient approach to efficiently enrich for mutations on multiple DNA targets and to enable prescreening before targeted resequencing.